Wax deposition mechanisms: Is the current description sufficient?. (1st September 2020) - Yang, Jinghao; Lu, Yingda; Daraboina, Nagu; Sarica, Cem
Highlights: Wax deposition can occur with oil temperatures equal to or lower than coolant. Prevailing molecular diffusion theory is not sufficient to explain this phenomenon. Soft Deposit formed primarily at the bottom of the pipe. Non-Newtonian feature of waxy crudes is essential to describing the deposition. Abstract: Wax deposition in subsea pipelines is one of the most challenging flow assurance issues during offshore oil and gas production, and applying appropriate and effective treatments depends on a thorough understanding of the physics of the wax deposition process. In most previous work, it is generally assumed that the oil temperature must be higher than the coolant temperature for wax deposition to occur. In this work, we present systematic experimental evidence that questions this prevailing understanding. An in-house pilot-scale flow loop was utilized to examine the deposition behavior of a waxy condensate with the bulk temperatures equal or lower than the coolant temperatures, under which conditions wax deposition is not supposed to occur. Surprisingly, considerable wax was deposited under all conditions examined. The deposit mass strongly depends on the operating conditions, with a higher deposition rate at lower coolant temperatures and lower flow rates. The deposits appear to be soft gels located primarily at the bottom of the pipe, with a carbon number distribution and wax content similar to those of the original oil. These observations, for the first time, provide consistent experimental evidence to demonstrate that molecular diffusion alone is not sufficient to describe wax deposition. We propose to consider the non-Newtonian features of waxy crude oils when describing wax deposition using molecular diffusion.